For this case we have the following system of equations:
![x + y = 5\\x - y = 7](https://img.qammunity.org/2021/formulas/mathematics/middle-school/uafgifj6yhbsawksiip0rp7fgswwkztfwe.png)
From the first equation we have:
![x = 5-y](https://img.qammunity.org/2021/formulas/mathematics/middle-school/5zxi8m45kltre8dviuzrqprqyopgh5glg8.png)
We substitute in the second equation:
![5-y-y = 7\\5-2y = 7](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ljgt5hchux011z73lwhmtyh1yjl1g21fx1.png)
We subtract 5 from both sides of the equation:
![-2y = 7-5\\-2y = 2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/tvke2m26n3ve9txwaqeiiclzp9b6omjhyb.png)
We divide -2 on both sides of the equation:
![y = \frac {2} {- 2}\\y = -1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/uktcrnp8uwhlgj3168xbk2zrvlqcakk1ef.png)
So:
![x = 5-y\\x = 5 - (- 1)\\x = 5 + 1\\x = 6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/o348250j5muotrrkdplf4hhapv8rebl6hc.png)
So, the system solution is:
![(x, y) :( 6, -1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/s3vdwmln16msrxdd1ib7vgk2jqcvqpwyd3.png)
Answer:
See attached image
![(x, y) :( 6, -1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/s3vdwmln16msrxdd1ib7vgk2jqcvqpwyd3.png)